Grit: Is It Required for Nursing Research?. (April 2020) - Florczak, Kristine L.
The following is a short introduction to the column concerning barriers and insights in recruiting participants for nursing research. It supports the notion that grit is required for nursing research and that consists of perseverance and passion.